Urgensi Kurikulum Merdeka dalam Moderasi Beragama Mahasiswa di PTKIN - Purnomo, Jumah; Ma'arij, Zafi Nur; Nursyiwan, Ilham (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2024)
This article discusses the urgency of the independent curriculum in supporting student religious moderation at State Islamic Religious Universities (PTKIN). The independent curriculum is considered important to integrate the values of religious moderation, such as tolerance, justice, and non-violence. This is crucial in the midst of the threat of radicalism among students. The research method used is literature review. Research is carried out by using library materials such as reference sources, books or other notes, known as literature research. The results and discussions of PTKIN are expected to play an important role in strengthening religious moderation through the implementation of an independent curriculum. This study identifies various PTKIN strategies in implementing religious moderation, including the establishment of the Religious Moderation House. However, the independent curriculum has a high urgency in supporting religious moderation at State Islamic Religious Universities (PTKIN). More optimal efforts are needed to integrate religious moderation in PTKIN's curriculum and academic activities.